Perencanaan Strategik dalam Membangun Mutu Pendidikan di Madrasah Syaichona Kholil Teluk Pandan - Setiyati, Setiyati; Tarman, Tarman; Metta, Metta; Warman, Warman (Jurnal Tarbiyah dan Ilmu Keguruan Borneo, 2024)
Educational planning within schools especially at Islamic school plays a pivotal role in shaping the academic journey and overall development of students. This article explores various facets of effective educational planning and its significance in fostering a conducive learning environment. Through a comprehensive review of literature and case studies, the article delves into the importance of long-term strategic planning, curriculum alignment, and resource allocation in achieving educational objectives. Additionally, it examines the role of stakeholder engagement and collaboration in the planning process, emphasizing the need for inclusive decision-making to address diverse student needs. Furthermore, the article discusses the integration of technology and data-driven approaches in educational planning, highlighting their potential to enhance efficiency and effectiveness. By elucidating these key elements, this article aims to provide insights and practical strategies for educators and school administrators to optimize educational planning and facilitate holistic student development.